COMPARISON OF SELECTED HEALTH AND MORPHOLOGICAL PARAMETERS BETWEEN CLASSIC SWIMMING AND SYNCHRONIZED SWIMMING - Lucija Dodigović,; Joško Sindik, (Sport Scientific And Practical Aspects, 2025)
Swimming and synchronized swimming are two similar sports, different in required patterns of movements, but with similar predispositions in important motor abilities, functional capacities and morphology. First goal in this study is to determine the differences between female girls in two age groups, activelyengaged in classic and synchronized swimming in chosen health and morphological parameters, as well se to forecast body mass index (BMI) in overall sample of active athletes with same parameters as the predictors.The data are collected from routine medical examinations of the athletes in the Polyclinic for Occupational Health and Sport in Zagreb, including sample of female athletes: swimmers (N=46) and synchronized swimmers (N=15), in two age groups: 7-13 yearsand13-15 years.The results showed that the differences between swimmers and synchronized swimmers are not found, except in the age group 7-13 years, where diastolic blood pressure and hematocrits showed higher mean values in synchronized swimmers, as compared to the swimmers. BMI could be successfully predicted on the base of only one statistically significant predictor (hemoglobin). Results offer the guidelines for improving the training process for both sports.